Al-Qur'an Tahfidz Program in Embedding Independent Learning Religiosity SMA Muhammadiyah 2 Surakarta: Program Tahfidz Al-Qur’an Dalam Menanamkan Religiusitas Merdeka Belajar SMA Muhammadiyah 2 Surakarta - Tamami, Fauziyah Qurrota Ayun; Aprilliano, Moza; Anggraeni, Puput; Rahmawati, Siti; Mustafa, Triono Ali (Prosiding University Research Colloquium, 2023)
This research uses a qualitative approach with field analysis (field research) and phenomenology with observation and interviews. The superior program of tahfidz al-Qur'an at SMA Muhammadiyah 2 Surakarta is the latest flagship program transformation of the extracurricular program. The research aim to discover how SMA Muhammadiyah 2 Surakarta instills religiosity in Merdeka learners through the Tahfidz Al-Qur'an program. The subjects of this research are the Deputy Principal of the Curriculum Section, Tahfidz Program Coordinator Teacher, and students of SMA Muhammadiyah 2 Surakarta. According to the results of this study, Muhammadiyah 2 Surakarta High School has implemented Merdeka Belajar through the Qur'an memorization program, which has been implemented for about one year and can instillthe religiosity value of Merdeka Belajar. It can be concluded that SMA Muhammadiyah 2 Surakarta is capable and has implemented the first Pancasila Student Profile of Merdeka Belajar according to the Merdeka Curriculum through various programs it implements, one of which is the superior program of tahfidz Al-Qur'an. It is hoped that this research for further research will be able to examine what is still lacking from this research in the sense that the research that has been conducted still requires further upgraded research.